SERVICE PERFORMANCE ANALYSIS OF PT PNM (CIVIL NATIONAL CAPITAL) SERVICES ULAMM (MICRO CAPITAL SERVICES UNIT) LHOKSEUMAWE CITY - Nurzarina, Maudi; Dhea Fidela , Cut; fayza, Adinda; Safriati, Safriati; Sinta, Irada (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine how much influence Service Performance has on customers' decisions to use murabahah financing products in the Lhokseumawe sharia micro capital service unit (ULaMM). PT. Permodalan Nasional Madani (Persero), with a Sharia micro capital service unit (ULaMM) unit Lhoseumawe is ready to provide sharia micro business capital that will be given to the public starting from Rp. 1,000,000, - up to Rp. 200,000,000. After this research is carried out, it is hoped that it will provide benefits to several parties, including increasing knowledge and insight related to sharia labels, location, and the need for customer decision making to use murabahah financing products.Data Analysis Method The analysis used in this study is descriptive qualitative analysis. The type of data consists of qualitative data, which is data that is not in the form of numbers. The data sources consist of primary data which are data from the first source and secondary data which are data obtained from indirect or second sources